2016
DOI: 10.1093/jjco/hyv204
|View full text |Cite
|
Sign up to set email alerts
|

ReducedmiR-215expression predicts poor prognosis in patients with acute myeloid leukemia

Abstract: Objective: Abnormal expression of microRNA-215 has been identified in a variety of solid cancers. However, little is known about the expression pattern of microRNA-215 in acute myeloid leukemia. This study was to investigate the status of microRNA-215 expression and further analyze its clinical significance in acute myeloid leukemia. Methods: Real-time quantitative polymerase chain reaction assay was performed to evaluate the expression level of microRNA-215 in 113 patients with acute myeloid leukemia. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…It has been found that miR-215 function as tumor suppressors in multiple cancers including gastric cancer, colon cancer, breast cancer, lung cancer, renal cell carcinoma acute myeloid leukemia, and glioma (32)(33)(34)(35)(36)(37)(38)(39)(40). As one of the P53-inducable miRNAs (23,24), miR-215 takes part in cancer development and progression through targeting YY-1, KDM1B, ZEB2, AKT1, XIAP, and RB1 (32)(33)(34)(35)(36)(37)(38)(39)(40). Interestingly, miR-215 is also a hypoxia-induced miRNA in glioma and vital for reprograming glioma-initiating cells to fit the hypoxic microenvironment via suppressing the expression of an epigenetic regulator KDM1B and modulating activities of multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that miR-215 function as tumor suppressors in multiple cancers including gastric cancer, colon cancer, breast cancer, lung cancer, renal cell carcinoma acute myeloid leukemia, and glioma (32)(33)(34)(35)(36)(37)(38)(39)(40). As one of the P53-inducable miRNAs (23,24), miR-215 takes part in cancer development and progression through targeting YY-1, KDM1B, ZEB2, AKT1, XIAP, and RB1 (32)(33)(34)(35)(36)(37)(38)(39)(40). Interestingly, miR-215 is also a hypoxia-induced miRNA in glioma and vital for reprograming glioma-initiating cells to fit the hypoxic microenvironment via suppressing the expression of an epigenetic regulator KDM1B and modulating activities of multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A number of biomarkers are currently used for the diagnosis, prognosis evaluation and treatment strategy of patients with AML, including karyotype, molecular classifications and mutation analysis (2). Classically, specific recurrent chromosomal translocations, including inversion (16) [inv (16)], translocation (8;21) [t(8;21)] and t (15;17) indicate a positive prognosis, while chromosomal deletions (dels) including del(5q), -5 and -7 are associated with more severe disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of evidence has indicated that ncRNAs such as circRNAs play an important role in leukemogenesis [19][20][21]; thus, circRNA-based therapy is a feasible approach for the treatment of AML. Aberrant circRNA expression has been associated with the malignant …”
Section: Discussionmentioning
confidence: 99%